Investigation of potassium and copper decorations of Carajás hematite on coal-fuelled chemical looping combustion performance. (15th February 2021) - Yan, Jingchong; Jiao, Hanren; Chu, Xiaogang; Lei, Zhiping; Kang, Shigang; Li, Zhanku; Wang, Zhicai; Ren, Shibiao; Shui, Hengfu
Highlights: Carajás hematite can be moderately reactive oxygen carrier in CF-CLC. K2 CO3 promotes carbon conversion but lowers CO2 selectivity in CF-CLC. CuO effectively and stably enhances CF-CLC performance of the hematite. CuO is superior to K2 CO3 for hematite decoration in CF-CLC. Abstract: Coal fuelled-chemical looping combustion (CF-CLC) is a novel and promising technology for CO2 mitigation. Reactive, cheap and environmental-friendly oxygen carriers (OC) are crutial for the development of CF-CLC. Carajás hematite is high grade iron ore with the largest reserve in the world, and its CF-CLC performance is examined in this work. Modifications of the Carajás hematite with K2 CO3 and CuO were performed and the effects of the modifications were evaluated. The results show that Carajás hematite was moderately reactive and could be potential OC for CF-CLC. Decoration of the Carajás hematite with K2 CO3 effectively improved carbon conversion but lowered CO2 selectivity. K2 CO3 was gradually lost thus reducing the performance of the decorated hematite. In addition, hematite particles were sintered after adding K2 CO3 . CuO remarkably enhanced carbon conversion, reaction rate as well as CO2 selectivity, and the Cu-modified hematite remained stable and highly reactive although agglomeration occurred in CF-CLC cycles. Overall, CuO is superior to K2 CO3 for modification of Carajás hematite, and the CuO-decorated hematite is suitable and promising OC for CF-CLC.